Diseño de un sistema de riego por goteo para el cultivo de tomate riñón (Solanum Lycopersicum) en un sector del predio “Curu Curu” de la parroquia San Pedro de la Bendita, cantón Catamayo - Cabrera Criollo, Jorge Alberto (2023)
The agricultural property "Curu Curu" located in the parish of San Pedro de la Bendita, Catamayo canton, is characterized by the absence of technified irrigation, prevailing the traditional irrigation by gravity due to the scarce knowledge of the farmer. In order to overcome this limitation and diversify production, a drip irrigation system was designed for the cultivation of kidney tomato. The study was based on the hydrophysical characteristics of the soil, which revealed a clay loam texture (Fo Ac), with a bulk density (Da) of 1,60 g/cm3; field capacity (CC) of 12,86 %; and permanent wilting point (PMP) of 9,22 %. In the agronomic design, the total water requirement for the kidney tomato crop was 5,29 mm/day, a gross irrigation lamina of 6,85 mm/day, in an area of 5,400 m2, which was divided into 9 subunits of 600 m2. Irrigation application was programmed with a frequency of one day and an application time of 4,5 hours. For water distribution, self-compensating drippers with a flow rate of 1,6 l/h were used, arranged at 0,30 m intervals. In the hydraulic design, primary, secondary and tertiary conduction networks corresponding to the irrigation laterals were established, with nominal diameters of 50, 32 and 12 mm, respectively, calculated with the Blasius formula. Finally, a Pedrollo HFm 70C 1.5 HP electric pump was selected to ensure the necessary water supply and pressure throughout the system.